Strategi Pengembangan Tenaga Kerja dalam Meningkatkan Pelayanan Publik: Studi Kasus pada Kantor Desa Simpang Raya, Kecamatan Sungai Ambawang, Kabupaten Kubu Raya - Dewi, Santika; Firayanti, Yuni; Marhamah, Marhamah (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
This study aims to analyze workforce development strategies in improving the quality of public services at the Simpang Raya Village Office, Sungai Ambawang District, Kubu Raya Regency. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation. The data analysis process was carried out through data reduction, data presentation, and drawing as well as verifying conclusions. The results show that workforce development strategies in Simpang Raya Village are implemented through workforce planning, technical training, routine coaching, and work motivation. The village secretary plays a central role in coordinating human resource development, starting from competency inventory to designing relevant training programs. Transparent and accountable financial management supports the successful implementation of workforce development programs. In the fields of governance and community welfare, the strategies are focused on improving administrative skills, providing excellent service, managing social assistance, and empowering the community. Technical training enhances service speed and accuracy, routine coaching strengthens work culture, and work motivation increases the loyalty of village officials. Overall, the integrated workforce development strategies have proven to provide a positive impact on the effectiveness of public service delivery at the village level